Kuantitas dan Karakteristik Sampah Bahan Pangan : Studi Kasis Surabaya Selatan - Sabrinatus Amalia Gustannanda; Euis Nurul Hidayah; Aulia Ulfah Farahdiba (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Food loss can be defined as the reduction of food quantity at each stage of the food supply chain, particularly in the type of food consumed by humans. This study aims to directly measure the amount and composition of food waste in order to provide complete and detailed information, which can also be used as a reference in formulating policies or preventive actions. Measurement of the quantity and composition of waste refers to SNI 19-3964-1994 with a sampling process for seven consecutive days based on the EPA's "A Guide to Conducting and Analyzing a Food Waste Assessment." The sampling results show that the quantity of food waste for one week (7 days) at Wonokromo Market is 1.08 tons and for Mangga Dua Market it is 1.06 tons, with an average food waste produced at Wonokromo Market of 154.6 kg per day and at Mangga Dua Market of 152.7 kg per day. This number includes only the categories of vegetables, fruits, starchy foods, whole grains, oily fruits and grains, and meat. Vegetables are in the category of food waste with the highest percentage. waste characteristics obtained from laboratory tests with test parameters for water content, calorific value, and CHON.